2019
DOI: 10.1177/1077559519873975
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse and Assault in a Large National Sample of Children and Adolescents

Abstract: The present study sought to examine features of sexual abuse cases among a U.S. nationally representative sample of 13,052 children and adolescents, ages 0–17 years. The National Survey of Children’s Exposure to Violence was collected in three different years (2008, 2011, and 2014) via telephone interviews. Information about sexual abuse and assault was obtained from youth themselves (ages 10–17) or caregivers (for children ages 0–9) using the Juvenile Victimization Questionnaire. Results indicate most offense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 65 publications
(129 reference statements)
5
57
0
5
Order By: Relevance
“…More than three quarter of the respondents affirms that SH can take place anywhere, a victim or perpetrator can be any gender, can have psychological effect on the victim and perpetrator does not have to be an opposite gender. Our findings are constant with existing literature where it was observed that majority of their respondents agreed that SH can occur anywhere and does not have to be an opposite gender (Arya & Arya, 2019;Bendixen & Kennair, 2017;Espelage, Hong, Rinehart, & Doshi, 2016;Gewirtz-Meydan & Finkelhor, 2019); the perpetrator can be any gender and relatively someone the victim knows (AAUW, 2011). Similarly, it was also reported that the physiological effect of SH on victim is enormous which include their desire to discontinue their schooling while for others it increased their fear of being withdrawn especially if their peers or parents came to hear of any incident (Bendixen & Kennair, 2017;Goodman et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…More than three quarter of the respondents affirms that SH can take place anywhere, a victim or perpetrator can be any gender, can have psychological effect on the victim and perpetrator does not have to be an opposite gender. Our findings are constant with existing literature where it was observed that majority of their respondents agreed that SH can occur anywhere and does not have to be an opposite gender (Arya & Arya, 2019;Bendixen & Kennair, 2017;Espelage, Hong, Rinehart, & Doshi, 2016;Gewirtz-Meydan & Finkelhor, 2019); the perpetrator can be any gender and relatively someone the victim knows (AAUW, 2011). Similarly, it was also reported that the physiological effect of SH on victim is enormous which include their desire to discontinue their schooling while for others it increased their fear of being withdrawn especially if their peers or parents came to hear of any incident (Bendixen & Kennair, 2017;Goodman et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Results about abuse must, however, be interpreted with caution, because other studies suggest that children and youth are exposed to sexual abuse and assault in varied ways, and may not speak openly about it (Gewirtz-Meydan & Finkelhor, 2020).…”
Section: Physical Abusementioning
confidence: 96%
“…However, this figure is likely an underestimate of the true prevalence of CSA committed by another youth, as victims may not report the abuse for a variety of reasons (e.g., they may anticipate a lack of support or anger from their caregivers if they report the incident) [ 30 ]. When examining youth reports rather than official records, rates of sexual abuse by another youth (rather than an adult) rise to approximately 75% [ 31 ]. Thus, many cases of CSA among youths appear to be unreported and not identified by professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Females constitute a greater portion of youths with PSB in early childhood years and preteen years, but males become more likely to exhibit PSB during adolescence [ 28 ]. Male children were equally likely to be abused by youths with PSB, while female children are more likely to be abused by male youths with PSB [ 31 ]. However, further research on child victims of PSB is largely limited.…”
Section: Introductionmentioning
confidence: 99%